Distribution and control of weeds of the genus Cocklebur (Xanthium L.) - Kurdyukova, O.; Tyschuk, E. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The article presents the results of herbological monitoring of the species composition and the level of presence of weeds of the genus Cocklebur (Xanthium L.) in agrophytocenoses and unprocessed lands of the Steppes of Ukraine. Found 6 species of the genus Cocklebur (Xanthium L.): Xanthium orientale subsp. riparium (Celak.) Greuter, Xanthium orientale subsp. californicum (Greene) Greuter, Xanthium strumarium subsp. brasilicum (Vell.) O. Bolòs & Vigo, Xanthium pungens Wallr., Xanthium strumarium L., Xanthium spinosum L. The highest level of presence in agrophytocenoses and unprocessed lands differed Xanthium orientale subsp. riparium, X. strumarium subsp. brasilicum and X. orientale subsp. californicum.